Low-temperature nickel-containing steel welding joints
Patent Information
- Application Number
- KR1020247015467
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-12-17
- Publication Date
- 2026-09-02
- Estimated Expiration
- 2041-12-17
Smart Images

Figure 112024050300750-PCT00007_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a nickel-containing steel welded joint for low temperatures. Background Technology
[0002] 9% Ni steel and 7% Ni steel are used in tanks for liquefied natural gas (LNG) (sometimes referred to as LNG tanks), etc. Since LNG tanks are manufactured by welding steel materials and low-temperature toughness is required for weld joints, weld joints in which the base metal and weld metal are 9% Ni steel have been proposed (see, for example, Patent Document 1). Since steel with an austenitic structure has excellent low-temperature toughness, weld joints consisting of a weld metal with a Ni content of 40% or more and a base metal of 9% Ni steel have been proposed (see, for example, Patent Document 2).
[0003] However, hydrogen is a clean energy source and is converted into liquid hydrogen to increase transport efficiency, and is stored in tanks, etc. The boiling point of liquid hydrogen at 1 atmosphere is -253°C, and the temperature of LNG is -162°C. Since liquid hydrogen is at a lower temperature than LNG, tanks made of 9% Ni steel may lack toughness at -253°C. Regarding the base material of the tank, some of the inventors have proposed a nickel-containing steel for low temperatures with a higher Ni content than that of 9% Ni steel (see, for example, Patent Documents 3 to 12). Meanwhile, regarding the welded joint, a welded joint made of austenitic stainless steel suitable for tanks used for the transport and storage of liquid hydrogen has been proposed (see, for example, Patent Documents 13 and 14). Prior art literature
[0004] International Publication No. 2018 / 05 / 1823 International Publication No. 2017 / 145854 Japanese Patent Publication No. 2017-197790 Japanese Patent Publication No. 2017-197791 Japanese Patent Publication No. 2017-197792 Japanese Patent Publication No. 2017-197793 Japanese Patent Publication No. 2018-104792 Japanese Patent Publication No. 2018-104793 International Publication No. 2019 / 08 / 2322 International Publication No. 2019 / 08 / 2324 International Publication No. 2019 / 08 / 2325 International Publication No. 2019 / 08 / 2326 Japanese Patent Publication No. 2001-287077 Japanese Patent Publication No. 2015-171729 The problem to be solved
[0005] Conventionally, welded joints made of various steels and weld metals capable of use at low temperatures have been proposed. However, as a result of investigations by the inventors, it was found that it is not easy to ensure the toughness of welded joints at -253°C, which is the boiling point of liquid hydrogen. Taking these circumstances into account, the present invention aims to provide a low-temperature nickel-containing steel welded joint capable of use at low temperatures around -253°C. means of solving the problem
[0006] The inventors investigated the toughness of a welded joint at a low temperature of around -253°C, in which the base material is a steel with a Ni content higher than the conventional 9% and the weld metal has an austenite microstructure. As a result, it was found that the toughness at a low temperature of around -253°C is influenced by the strength of the base material. In addition, it was found that the low-temperature toughness of the welded joint is improved by controlling the hardness of the base material and the weld heat-affected zone (HAZ).
[0007] The present invention is based on the above findings, and its gist is as follows.
[0008] (1) A low-temperature nickel-containing steel weld joint according to one embodiment of the present invention has a base material, a weld heat-affected zone, and a weld metal, and
[0009] The chemical composition of the above base material is, in mass %,
[0010] C: 0.010% or more, 0.070% or less,
[0011] Si: 0.03% or more, 0.30% or less,
[0012] Mn: 0.10% or more, 0.80% or less,
[0013] Ni: 10.5% or more, 17.4% or less,
[0014] Al: 0.010% or more, 0.060% or less,
[0015] N: 0.0015% or more, 0.0060% or less,
[0016] O: 0.0030% or less,
[0017] P: 0.0080% or less,
[0018] S: 0.0040% or less,
[0019] Cu: 0% or more, 1.00% or less,
[0020] Cr: 0% or more, 1.00% or less,
[0021] Mo: 0% or more, 0.60% or less,
[0022] Nb: 0% or more, 0.050% or less,
[0023] V: 0% or more, 0.080% or less,
[0024] Ti: 0% or more, 0.020% or less,
[0025] B: 0% or more, 0.0020% or less,
[0026] Ca: 0% or more, 0.0040% or less,
[0027] REM: 0% or more, 0.0050% or less,
[0028] Remainder: Fe and impurities
[0029] It consists of,
[0030] The average value of the circular equivalent diameter of the old austenite in the above base material is 3.0㎛ or more and 20.0㎛ or less, and
[0031] The yield stress of the above base material at 20°C is 460 MPa or more and 710 MPa or less, and
[0032] The chemical composition of the above weld metal is, in mass %,
[0033] C: 0.01% or more, 0.30% or less,
[0034] Si: 0.03% or more, 0.75% or less
[0035] and,
[0036] Mn: 0.1% or more, 17.0% or less,
[0037] Ni: 8.0% or more, 85.0% or less
[0038] and,
[0039] P: 0.020% or less,
[0040] S: 0.015% or less,
[0041] N: 0.10% or less
[0042] and,
[0043] Mo: 0% or more, 22.0% or less,
[0044] W: 0% or more, 5.0% or less,
[0045] Cr: 0% or more, 17.0% or less,
[0046] Nb: 0% or more, 3.0% or less
[0047] At least one of these types totaling 2.0% or more, and,
[0048] O: 0% or more, 0.1% or less, and,
[0049] Remainder: Fe and impurities
[0050] It consists of,
[0051] The proportion of the body-centered cubic structure in the microstructure of the weld metal above is 10% or less.
[0052] (2) The low-temperature nickel-containing steel welded joint described in (1) above has a chemical composition of the weld metal in mass%,
[0053] C: 0.01% or more, 0.15% or less,
[0054] Si: 0.03% or more, 0.75% or less,
[0055] Mn: 0.1% or more, 4.0% or less,
[0056] Ni: 40.0% or more, 85.0% or less,
[0057] Mo: 9.0% or more, 22.0% or less,
[0058] W: 0.9% or more, 5.0% or less,
[0059] Cr: 0% or more, 4.0% or less,
[0060] Nb: 0% or more, 3.0% or less,
[0061] P: 0.020% or less,
[0062] S: 0.015% or less,
[0063] N: 0.010% or less,
[0064] O: 0% or more, 0.1% or less,
[0065] Remainder: Fe and impurities
[0066] It may be composed of.
[0067] (3) The low-temperature nickel-containing steel welded joint described in (1) above has a chemical composition of the weld metal in mass%,
[0068] C: 0.01% or more, 0.15% or less,
[0069] Si: 0.03% or more, 0.75% or less,
[0070] Mn: 0.1% or more, 4.0% or less,
[0071] Ni: 40.0% or more, 85.0% or less,
[0072] Cr: 6.0% or more, 17.0% or less,
[0073] Mo: 0% or more, 9.0% or less,
[0074] W: 0% or more, 5.0% or less,
[0075] Nb: 0.2% or more, 3.0% or less,
[0076] P: 0.020% or less,
[0077] S: 0.015% or less,
[0078] N: 0.010% or less,
[0079] O: 0% or more, 0.1% or less,
[0080] Remainder: Fe and impurities
[0081] It may be composed of.
[0082] (4) The low-temperature nickel-containing steel welded joint described in (1) above has a chemical composition of the weld metal in mass%,
[0083] C: 0.01% or more, 0.30% or less,
[0084] Si: 0.03% or more, 0.75% or less,
[0085] Mn: 7.0% or more, 17.0% or less,
[0086] Ni: 8.0% or more, 18.0% or less,
[0087] Cr: 2.0% or more, 12.0% or less,
[0088] Nb: 0% or more, 3.0% or less,
[0089] Mo: 0% or more, 5.0% or less,
[0090] W: 0% or more, 5.0% or less,
[0091] P: 0.020% or less,
[0092] S: 0.015% or less,
[0093] N: 0.10% or less,
[0094] O: 0% or more, 0.1% or less,
[0095] Remainder: Fe and impurities
[0096] It may be composed of.
[0097] (5) The low-temperature nickel-containing steel welded joint described in any one of (1) to (4) above is,
[0098] The maximum value of the Vickers hardness of the weld heat-affected zone is at least 1.20 times and no more than 3.00 times the arithmetic mean value of the Vickers hardness of the base metal and the Vickers hardness of the weld metal, and
[0099] The effective crystal grain size of the region where the Vickers hardness of the above-mentioned weld heat-affected zone is at its maximum value may be 2.0㎛ or more and 18.0㎛ or less. Effects of the invention
[0100] According to the present invention, a low-temperature nickel-containing steel welded joint usable at low temperatures around -253℃ is provided. Brief explanation of the drawing
[0101] FIG. 1 is a drawing for explaining an example of a nickel-containing steel welded joint for low temperature according to the present embodiment. Figure 2 is a diagram illustrating the location for measuring Vickers hardness. Figure 3 is a diagram illustrating the location of a notch introduced into a test specimen used to measure the cryogenic toughness of the weld heat-affected zone. Specific details for implementing the invention
[0102] Hereinafter, a low-temperature nickel-containing steel welded joint according to one embodiment of the present invention will be described. First, the novel findings obtained as a result of the inventors' examination leading to the completion of the present invention will be described in detail.
[0103] The toughness of 9% Ni steel used in LNG tanks was evaluated at -165°C or -196°C. The toughness of the nickel-containing steel welded joint for low temperatures (hereinafter abbreviated as "Ni steel joint") according to the present embodiment is evaluated at around -253°C, which is lower than -196°C. Hereinafter, in order to explain concisely and distinguish it from temperatures such as -165°C or -196°C, the temperature around -253°C is conveniently referred to as "ultra-low temperature."
[0104] FIG. 1 is a schematic diagram illustrating an example of a Ni steel joint according to the present embodiment. FIG. 1 shows a Ni steel joint in which the shape of the improvement is X-shaped and shows a cross-section perpendicular to the welding direction. The Ni steel joint according to the present embodiment has a base material part (1), a weld heat-affected zone (2), and a weld metal (3). The base material part (1), the weld heat-affected zone (2), and the weld metal (3) have different metal structures, and each part can be identified by a method based on JIS G 0553:2019 “Method for testing the macrostructure of steel”. Specifically, a sample is taken from the Ni steel joint by a method based on the above JIS standard, the observation surface is finished to a mirror surface by mechanical polishing and buff polishing, and etching is performed so that the base material part, the heat-affected zone, and the weld metal can be identified by the difference in contrast by the naked eye or a magnifying glass.
[0105] The inventors conducted an investigation to determine the influence of the base material, weld metal, and weld heat-affected zone on the toughness of a Ni steel joint at cryogenic temperatures (hereinafter referred to as "cryogenic toughness"). Among Ni steel with a Ni content equivalent to that of the base material, austenitic steel containing Mn and Ni, and high-Ni alloys containing 40% or more Ni, it was found that austenitic steel and high-Ni alloys were optimal for the weld metal. It was found that in the case of a Ni steel joint where the weld metal is austenitic steel containing Mn and Ni, or a high-Ni alloy, the toughness of the weld metal is higher than that of the base material and the HAZ.
[0106] At cryogenic temperatures, fracture is prone to occur at the old austenite grain boundaries of the base material, which can easily lead to a decrease in toughness. Old austenite grain boundaries are the austenite grain boundaries that existed primarily after hot rolling and before the start of water cooling during the manufacture of the base material. Among the old austenite grain boundaries, fracture from non-coarse old austenite grain boundaries is relatively difficult to occur. If the circular equivalent diameter of the old austenite in the base material is 20.0 μm or less, cryogenic toughness of the base material and the HAZ is secured. The strength of the base material affects the cryogenic toughness of the Ni steel joint. If the yield stress of the base material at room temperature (20°C) is 710 MPa or less, cryogenic toughness of the Ni steel joint is secured.
[0107] Furthermore, relieving stress concentration in the HAZ improves the cryogenic toughness of Ni-steel joints. When the hardness of the HAZ is higher than that of the base metal and weld metal, the base metal and weld metal deform preferentially over the HAZ, thereby relieving stress concentration in the HAZ. To improve the cryogenic toughness of Ni-steel joints, it is desirable for the Vickers hardness of the HAZ to be greater than that of the weld metal and base metal.
[0108] In addition, the effective grain size of the region where the Vickers hardness of the HAZ is at its maximum is preferably fine to improve the cryogenic toughness of the Ni steel joint.
[0109] Up to this point, new findings obtained through the inventors' review have been explained.
[0110] [Mojaebu]
[0111] Next, the chemical composition of the base material of the Ni steel joint according to the present embodiment will be described. Unless otherwise noted, the following description of the chemical composition describes the chemical composition of the base material, and "mass%" is indicated as "%".
[0112] (C: 0.010% or more, 0.070% or less)
[0113] C is an element that increases the yield stress of the base material at room temperature and also contributes to the formation of martensite or austenite. The C content is 0.010% or more from the perspective of increasing the strength of the base material to secure the overall strength of the Ni steel joint. The C content is preferably 0.020% or more, and more preferably 0.040% or more. On the other hand, if the C content is excessive, the cryogenic toughness of the base material decreases due to the formation of cementite, thereby reducing the cryogenic toughness of the Ni steel joint. The C content is 0.070% or less from the perspective of securing the cryogenic toughness of the Ni steel joint. The C content is preferably 0.060% or less, and more preferably 0.050% or less.
[0114] (Si: 0.03% or more, 0.30% or less)
[0115] Si is an element that increases the yield stress of the base material at room temperature. The Si content is 0.03% or more from the perspective of increasing the strength of the base material to secure the overall strength of the Ni steel joint. The Si content is preferably 0.04% or more, and more preferably 0.05% or more. On the other hand, Si is an element that lowers toughness. The Si content is 0.30% or less from the perspective of suppressing the decrease in cryogenic toughness of the base material to secure the cryogenic toughness of the Ni steel joint. The Si content is preferably 0.20% or less, and more preferably 0.10% or less.
[0116] (Mn: 0.10% or more, 0.80% or less)
[0117] Mn is an element that increases the yield stress of the base material at room temperature. The Mn content is 0.10% or more from the perspective of securing the strength of the Ni steel joint by increasing the yield stress of the base material at room temperature. The Mn content is preferably 0.25% or more, and more preferably 0.30% or more. Meanwhile, Mn is an element that forms MnS, and if the Mn content is excessive, the cryogenic toughness of the base material is reduced due to segregation of Mn at the old austenite grain boundaries or precipitation of coarse MnS, thereby reducing the cryogenic toughness of the Ni steel joint. The Mn content is 0.80% or less from the perspective of securing the cryogenic toughness of the Ni steel joint. The Mn content is preferably 0.70% or less, and more preferably 0.60% or less. The Mn content may be 0.40% or less.
[0118] (Ni: 10.5% or more, 17.4% or less)
[0119] Ni is an important element for improving the cryogenic toughness of steel. The Ni content is 10.5% or more from the perspective of ensuring the cryogenic toughness of Ni steel joints. The Ni content is preferably 11.0% or more, and more preferably 11.5% or more. Since Ni is an expensive element, the Ni content is 17.4% or less from the perspective of economic feasibility. The Ni content is preferably 15.4% or less, more preferably 14.4% or less, and even more preferably 12.4% or less.
[0120] (Al: 0.010% or more, 0.060% or less)
[0121] Al is a deoxidizer and an element that forms AlN. The Al content is 0.010% or more from the perspective of the deoxidation effect, the refinement of the metal structure by AlN, and the reduction of dissolved N which lowers the cryogenic toughness of the base material. The Al content is preferably 0.015% or more, and more preferably 0.020% or more. On the other hand, if the Al content is excessive, the cryogenic toughness of the base material is reduced due to inclusions, and the cryogenic toughness of the Ni-steel joint is reduced. The Al content is 0.060% or less from the perspective of ensuring the cryogenic toughness of the Ni-steel joint. The Al content is preferably 0.040% or less, and more preferably 0.035% or less.
[0122] (N: 0.0015% or more, 0.0060% or less)
[0123] N is an element that forms nitrides. The N content is 0.0015% or more from the perspective of grain refinement by nitrides. The N content is preferably 0.0020% or more. On the other hand, if the N content is excessive, the cryogenic toughness of the base material decreases due to an increase in dissolved N and coarsening of nitrides, thereby reducing the cryogenic toughness of the Ni steel joint. The N content is 0.0060% or less from the perspective of ensuring cryogenic toughness of the Ni steel joint. The N content is preferably 0.0050% or less, more preferably 0.0040% or less, and even more preferably 0.0035% or less.
[0124] (O: 0.0030% or less)
[0125] O is an impurity, and if the O content is excessive, Al2O3 clusters increase, which may lead to a decrease in the cryogenic toughness of the base material. The O content is 0.0030% or less from the perspective of ensuring cryogenic toughness of the Ni steel joint. The O content is preferably 0.0025% or less, more preferably 0.0020% or less, and even more preferably 0.0015% or less. While it is preferable for the O content to be as low as possible, from the perspective of cost, it may be 0.0007% or more. The O content may be 0.0008% or more, or 0.0010% or more.
[0126] (P: 0.0080% or less)
[0127] P is an impurity, and if the P content is excessive, the cryogenic toughness of the base material may decrease due to intergranular embrittlement at the prior austenite grain boundaries. The P content is 0.0080% or less from the perspective of ensuring cryogenic toughness of the Ni steel joint. The P content is preferably 0.0070% or less, more preferably 0.0050% or less, and even more preferably 0.0040% or less. While it is preferable for the P content to be as low as possible, it may be 0.0003% or more from the perspective of cost. The P content may be 0.0005% or more, or 0.0010% or more.
[0128] (S: 0.0040% or less)
[0129] S is an impurity and an element that forms MnS; if the S content is excessive, the cryogenic toughness of the base material may decrease due to the coarsening of MnS. The S content is 0.0040% or less from the perspective of suppressing the decrease in cryogenic toughness of the base material and securing the cryogenic toughness of the Ni steel joint. The S content is preferably 0.0030% or less, more preferably 0.0020% or less, and even more preferably 0.0010% or less. While it is preferable for the S content to be lower, it may be 0.0001% or more from the perspective of cost. The S content may be 0.0002% or more, 0.0004% or more, or 0.0006% or more.
[0130] The base material of the Ni steel joint according to the present embodiment may contain one or more of the following optional elements Cu, Cr, Mo, Nb, V, Ti, and B as needed to improve its strength or toughness.
[0131] (Cu: 0% or more, 1.00% or less)
[0132] Cu is an element that is incorporated into the base material during the manufacture of the base material used for the Ni-steel joint, and as a result, may be incorporated into the base material portion of the Ni-steel joint. The lower limit of the Cu content is not limited and may be 0%. Cu is an element that contributes to the formation of martensite or austenite, and the Cu content may be 0.02% or more from the perspective of increasing the yield strength of the base material portion at room temperature. The Cu content is preferably 0.05% or more, and more preferably 0.10% or more. On the other hand, the Cu content when Cu is included is 1.00% or less from the perspective of ensuring cryogenic toughness of the Ni-steel joint. The Cu content is preferably 0.50% or less, more preferably 0.40% or less, and even more preferably 0.20% or less.
[0133] (Cr: 0% or more, 1.00% or less)
[0134] Cr is an element that is incorporated into the base material during the manufacture of the base material used for the Ni-steel joint, and as a result, may be incorporated into the base material portion of the Ni-steel joint. The lower limit of the Cr content is not limited and may be 0%. Cr is an element that increases the quenchability of steel, and the Cr content may be 0.02% or more from the perspective of increasing the yield strength of the base material portion at room temperature. The Cr content is preferably 0.05% or more, and more preferably 0.10% or more. On the other hand, if Cr is contained in excess, coarse carbides may be formed in the base material, which may reduce the cryogenic toughness of the Ni-steel joint. The Cr content when Cr is included is 1.00% or less from the perspective of ensuring the cryogenic toughness of the Ni-steel joint. The Cr content is preferably 0.50% or less, more preferably 0.40% or less, and even more preferably 0.20% or less.
[0135] (Mo: 0% or more, 0.60% or less)
[0136] Mo is an element that is incorporated into the base material during the manufacture of the base material used for Ni-steel joints, and as a result, may be incorporated into the base material portion of the Ni-steel joint. The lower limit of the Mo content is not limited and may be 0%. Mo is an element that increases the quenchability of steel and suppresses intergranular embrittlement. The Mo content may be 0.02% or more from the perspective of improving the yield strength at room temperature and cryogenic toughness of the base material portion. The Mo content is preferably 0.05% or more, more preferably 0.10% or more, and even more preferably 0.20% or more. On the other hand, Mo is an expensive element, and the Mo content when Mo is included is 0.60% or less from the perspective of economic feasibility. The Mo content is preferably 0.40% or less, more preferably 0.35% or less, and even more preferably 0.30% or less.
[0137] (Nb: 0% or more, 0.050% or less)
[0138] Nb is an element that is incorporated into the base material during the manufacture of the base material used for the Ni-steel joint, and as a result, may be incorporated into the base material of the Ni-steel joint. The lower limit of the Nb content is not limited and may be 0%. Nb is an element that forms carbides, nitrides, etc., and contributes to precipitation strengthening, thereby refining the metal structure. The Nb content may be 0.002% or more from the perspective of improving the yield strength at room temperature and cryogenic toughness of the base material. The Nb content is preferably 0.005% or more, and more preferably 0.008% or more. On the other hand, if the Nb content is excessive, the cryogenic toughness of the base material may decrease due to precipitates. The Nb content when Nb is included is 0.050% or less from the perspective of suppressing the decrease in cryogenic toughness of the base material and securing the cryogenic toughness of the Ni-steel joint. The Nb content is preferably 0.020% or less, and more preferably 0.015% or less.
[0139] (V: 0% or more, 0.080% or less)
[0140] V is an element that is incorporated into the base material during the manufacture of the base material used for the Ni-steel joint, and as a result, may be incorporated into the base material of the Ni-steel joint. The lower limit of the V content is not limited and may be 0%. V is an element that forms carbides, nitrides, etc., and contributes to precipitation strengthening, thereby refining the metal structure. The V content may be 0.002% or more from the perspective of improving the yield strength at room temperature and cryogenic toughness of the base material. The V content is preferably 0.005% or more, and more preferably 0.010% or more. On the other hand, if the V content is excessive, the cryogenic toughness of the base material may decrease due to precipitates. The V content when V is included is 0.080% or less from the perspective of suppressing the decrease in cryogenic toughness of the base material and securing the cryogenic toughness of the Ni-steel joint. The V content is preferably 0.060% or less, and more preferably 0.040% or less.
[0141] (Ti: 0% or more, 0.020% or less)
[0142] Ti is an element that is incorporated into the base material during the manufacture of the base material used for the Ni-steel joint, and as a result, may be incorporated into the base material of the Ni-steel joint. The lower limit of the Ti content is not limited and may be 0%. Ti is an element that forms TiN, and contributes to the refinement of the metal structure and the reduction of dissolved nitrogen, thereby improving the toughness of the base material. From the perspective of improving the cryogenic toughness of the Ni-steel joint, the Ti content may be 0.001% or more. The Ti content is preferably 0.002% or more, and more preferably 0.005% or more. On the other hand, if the Ti content is excessive, the cryogenic toughness of the base material may decrease due to the coarsening of TiN. From the perspective of suppressing the decrease in cryogenic toughness of the base material and securing the cryogenic toughness of the Ni-steel joint, the Ti content is 0.020% or less. The Ti content is preferably 0.015% or less, and more preferably 0.010% or less.
[0143] (B: 0% or more, 0.0020% or less)
[0144] B is an element that is incorporated into the base material during the manufacture of the base material used for the Ni-steel joint, and as a result, may be incorporated into the base material of the Ni-steel joint. The lower limit of the B content is not limited and may be 0%. B is an element that significantly increases the quenchability of steel and contributes to the reduction of dissolved N by forming BN. The B content may be 0.0001% or more from the perspective of improving the yield strength at room temperature and cryogenic toughness of the base material. The B content is preferably 0.0003% or more, and more preferably 0.0005% or more. On the other hand, if the B content is excessive, the cryogenic toughness of the base material may decrease. The B content is 0.0020% or less from the perspective of suppressing the decrease in cryogenic toughness of the base material and securing the cryogenic toughness of the Ni-steel joint. The B content is preferably 0.0015% or less, more preferably 0.0012% or less, and even more preferably 0.0010% or less.
[0145] The base material of the Ni steel joint according to the present embodiment may contain one or both of the following optional elements, Ca and REM (Rare Earth Metal), as needed for the purpose of controlling the shape of inclusions.
[0146] (Ca: 0% or more, 0.0040% or less)
[0147] Ca is an element that is incorporated into the base material during the manufacture of the base material used for the Ni-steel joint, and as a result, may be incorporated into the base material portion of the Ni-steel joint. The lower limit of the Ca content is not limited and may be 0%. Ca is an element that forms oxides and sulfides, and it contributes to the improvement of cryogenic toughness of the base material by suppressing the coarsening of inclusions and the elongation of inclusions caused by rolling. The Ca content may be 0.0001% or more from the perspective of improving the cryogenic toughness of the base material and thereby improving the cryogenic toughness of the Ni-steel joint. The Ca content is preferably 0.0005% or more, and more preferably 0.0010% or more. On the other hand, if the Ca content is excessive, the cryogenic toughness of the base material decreases due to inclusions. The Ca content is 0.0040% or less from the perspective of securing the cryogenic toughness of the Ni-steel joint by suppressing the decrease in cryogenic toughness of the base material. The Ca content is preferably 0.0035% or less, and more preferably 0.0030% or less.
[0148] (REM: 0% or more, 0.0050% or less)
[0149] REM (rare earth metal elements) consists of a total of 17 elements, including Sc, Y, and lanthanides, and as REM, one or more elements selected from the group consisting of Sc, Y, and lanthanides are contained. The REM content is the total content of the above elements contained in the base material among these 17 elements. REM is an element that is incorporated into the base material during the manufacture of the base material that is the material for the Ni steel joint, and as a result, may be incorporated into the base material of the Ni steel joint. The lower limit of the REM content is not limited and may be 0%. REM is an element that forms oxides and sulfides and contributes to the refinement of inclusions, thereby contributing to the improvement of cryogenic toughness of the base material. The REM content may be 0.0001% or more from the perspective of improving the cryogenic toughness of the Ni steel joint by improving the cryogenic toughness of the base material. The REM content is preferably 0.0005% or more, more preferably 0.0010% or more, and even more preferably 0.0015% or more. From the perspective of cost, the REM content is 0.0050% or less. The REM content is preferably 0.0040% or less.
[0150] The base material of the nickel steel joint of the present embodiment contains the above chemical components, and the remainder consists of Fe and impurities. The total content of the above chemical components is preferably 96.0% or less, more preferably 90.0% or less, and even more preferably 80.0% or less. Here, impurities refer to chemical components that are incorporated due to various factors of the manufacturing process, including raw materials such as ore or scrap, when steel is manufactured industrially, and are permitted within a range that does not adversely affect the base material and the Ni steel joint in the present embodiment. Chemical components that may be incorporated from scrap, etc. include, for example, Sb, Sn, As, Co, Zn, W, etc. The Sb content, Sn content, and As content permitted within a range that does not adversely affect the base material and the Ni steel joint in the present embodiment are each 0.003% or less. Similarly, the Co content and Zn content are each 0.01% or less, and the W content is 0.005% or less.
[0151] Next, the metal structure of the base material in this embodiment will be described.
[0152] (Average value of the circular equivalent diameter of the old austenite: 3.0㎛ or more, 20.0㎛ or less)
[0153] The average value of the circular equivalent diameter of the old austenite in the base material portion according to the present embodiment is 20.0 μm or less from the perspective of securing cryogenic toughness. The average value of the circular equivalent diameter of the old austenite is preferably 15.0 μm or less, and more preferably 10.0 μm or less. The old austenite in the base material portion of the Ni steel joint is refined by means that entail an increase in manufacturing costs. Therefore, the average value of the circular equivalent diameter of the old austenite is 3.0 μm or more from the perspective of cost. The average value of the circular equivalent diameter of the old austenite may be 4.0 μm or more, or 5.0 μm or more.
[0154] The average value of the circular equivalent diameter of the old austenite is measured by EBSD (electron back scattering diffraction) analysis using a scanning electron microscope (hereinafter referred to as "SEM"), with the center of the plate thickness direction (the center of the plate thickness) in the L cross-section (a plane parallel to the rolling direction and the plate thickness direction) as the observation surface. The center of the plate thickness referred to here refers to the range from a depth of 0.4t from one surface of the base material to a depth of 0.6t, where the plate thickness of the base material is t. The observation surface of the sample is mirror-polished and etched with a saturated aqueous picric acid solution to reveal the old austenite grain boundaries. SEM observation is performed at a magnification of 1000x or 2000x, and SEM images of at least 5 fields of view are captured. The average value of the circular equivalent diameter of the old austenite is the arithmetic mean of the measured values obtained by image processing using the SEM images. Image processing is performed by the following method. Specifically, the grain boundaries of the former austenite are determined by EBSD analysis by specifying the crystal orientations of martensite and retained austenite within a 200 µm × 200 µm range in each field of view, and the crystal orientations of the former austenite within the said range are determined. Lines where the difference in crystal orientation of the former austenite is 15° or greater are defined as the grain boundaries of the former austenite. The area of the former austenite existing within the said range of each field of view is calculated using image analysis software, and from the calculated area S, the average value S of the area of the former austenite A Calculate. Then, let D be the average value of the circular equivalent diameter of the spherical austenite, and D=2×√(π×S A From ), the average value D of the original equivalent diameter of the austenite is calculated. In addition, the observation surface may be cut from the base material portion of the Ni steel joint, or may be cut from the base material of the Ni steel joint.
[0155] In cases where the grain boundaries of the old austenite cannot be determined by mirror polishing and corrosion with a saturated aqueous picric acid solution, a sample that has undergone a heat treatment held at a temperature within the range of 450°C to 490°C for at least one hour, and has been subjected to mirror polishing and corrosion with a saturated aqueous picric acid solution, is used. If the grain boundaries of the old austenite do not appear even after such sample preparation, the original diameter of the old austenite is measured by observing the fracture surface of a sample in which grain boundary fracture was caused by a Charpy impact test. For the Charpy impact test, a Charpy test specimen taken from a sample that has undergone a heat treatment held at a temperature within the range of 450°C to 490°C for at least one hour is used, and the test is performed at -196°C. The Charpy test specimen shall conform to JIS Z 2242:2018.
[0156] The metal structure of the base material in this embodiment is mainly tempered martensite, and may include austenite. The total volume fraction of tempered martensite and austenite in the metal structure at the center of the plate thickness is 99% or more, and the remainder is, for example, coarse inclusions. The volume fraction of tempered martensite is the area fraction measured by observing the microstructure of a plane parallel to the rolling plane at the center of the plate thickness, which has been etched using Nital as the etching solution. From the perspective of quantitative microscopy, the area fraction is basically the same as the volume fraction. The austenite included in the metal structure of the base material is so-called retained austenite.
[0157] The volume fraction of the retained austenite phase in the base material is preferably 2.0 volume% or more and 20.0 volume% or less from the perspective of improving the cryogenic toughness of the Ni steel joint. The volume fraction of the retained austenite is measured by X-ray diffraction. The volume fraction of the retained austenite is obtained from the ratio of the integrated intensity of the austenite (face-centered cubic structure) and the tempered martensite (body-centered cubic structure) X-ray peaks. Specifically, the volume fraction of the retained austenite is obtained from the ratio of the integrated intensity of the (111), (200), and (211) planes of the ferrite phase (α phase) with a BCC structure to the integrated intensity of the (111), (200), and (220) planes of the austenite phase (γ phase) with an FCC structure. In addition, the test specimen may be cut from the base material portion of the Ni steel joint, or may be cut from the base material of the Ni steel joint.
[0158] Next, the plate thickness of the base material and the yield stress at 20°C (room temperature) in this embodiment will be explained.
[0159] (Yield stress at 20℃: 460 MPa or more, 710 MPa or less)
[0160] In this embodiment, the yield stress of the base material at room temperature is 460 MPa or higher, considering that the base material is used as a material for large structures such as liquid hydrogen tanks. On the other hand, the yield stress of the base material at room temperature is 710 MPa or lower, considering the securing of cryogenic toughness of the Ni-steel joint. In this embodiment, the test temperature is 20°C. The test temperature is controlled by an air conditioner. The tensile test is performed in accordance with JIS Z 2241:2011. In addition, the test specimen may be cut from the base material of the Ni-steel joint, or may be cut from the base material of the Ni-steel joint.
[0161] (Plate thickness: 4.5 mm or more, 20.0 mm or less)
[0162] In this embodiment, since the Ni steel is used as a material for large structures such as liquid hydrogen tanks, the plate thickness of the Ni steel is, for example, 4.5 mm or more. The plate thickness may be 6 mm or more, 8 mm or more, or 10 mm or more. On the other hand, if the plate thickness of the Ni steel increases, the cryogenic toughness may decrease. The plate thickness of the Ni steel is, for example, 20.0 mm or less. The plate thickness of the Ni steel may be 16 mm or less, or 12 mm or less.
[0163] [Welding Heat Affected Zone (HAZ)]
[0164] Next, the weld heat-affected zone (HAZ) of the Ni steel joint according to the present embodiment will be described.
[0165] The HAZ is a region located near the weld metal that is heat-affected by the welding heat input. It is possible to distinguish between the base metal, the HAZ, and the weld metal by observing the macrostructure using Nital as an etchant. The weld metal of the Ni steel joint according to the present embodiment is an austenitic steel with excellent cryogenic toughness or a high-Ni alloy containing Ni, and does not serve as a starting point for fracture. The HAZ of the Ni steel joint according to the present embodiment has an embrittled region in which the Vickers hardness is higher than that of the base metal. The embrittled region is a region where the Vickers hardness is higher than that of the base metal and the Vickers hardness of the HAZ reaches its maximum value.
[0166] (Maximum Vickers hardness of HAZ: Greater than the Vickers hardness of the base metal and weld metal)
[0167] (Maximum Vickers hardness of HAZ: 1.20 times or more and 3.00 times or less of the arithmetic mean of the Vickers hardness of the base metal and the weld metal)
[0168] It is desirable that the maximum Vickers hardness of the HAZ be greater than the Vickers hardness of the base metal and the weld metal. When the maximum Vickers hardness of the HAZ is greater than the Vickers hardness of the base metal and the weld metal, stress concentration in the HAZ is relieved by deformation of the weld metal and the base metal, thereby improving the toughness of the Ni steel joint. From the perspective of improving the cryogenic toughness of the Ni steel joint, the maximum Vickers hardness of the HAZ is preferably 1.20 times or more the arithmetic mean of the Vickers hardness of the base metal and the Vickers hardness of the weld metal. The maximum Vickers hardness of the HAZ may be 1.30 times or more, or 1.40 times or more, the arithmetic mean of the Vickers hardness of the base metal and the weld metal. On the other hand, due to the hardening of the HAZ, fracture may occur more easily in the HAZ, and the toughness of the Ni steel joint may decrease. The maximum value of the Vickers hardness of the HAZ is preferably 3.00 times or less the arithmetic mean of the Vickers hardness of the base metal and the Vickers hardness of the weld metal, from the perspective of improving the cryogenic toughness of the Ni steel joint. It is more preferable that the maximum value of the Vickers hardness of the HAZ is 2.50 times or less the arithmetic mean of the Vickers hardness of the base metal and the Vickers hardness of the weld metal, and even more preferable that it is 2.00 times or less.
[0169] The Vickers hardness of the base metal, HAZ, and weld metal in the Ni steel joint according to the present embodiment is measured at the locations described below. In cases where the root face of the weld metal groove is in direct contact with the surface of the base metal, such as a single V groove, a single bevel groove, a single J groove, or a single U groove, the measurement is taken at a position t / 2 from the surface when the plate thickness is t (t / 2 part). In cases where the root face of the weld metal groove includes the t / 2 part, such as an X groove, a double bevel groove, a double J groove, or a double U groove, the measurement is taken at a position t / 4 from the surface when the plate thickness is t (t / 4 part). When the root face of the weld metal improvement is located between the surface and the t / 2 portion, the measurement is taken at a position where the distance from the center of the root face in the plate thickness direction to the surface on the far side is 1 / 2. The reason for setting the measurement position for Vickers hardness in this way is that it represents the typical hardness when the evaluation position includes half of the weld metal and half of the base metal.
[0170] The measurement of Vickers hardness of the base material, HAZ, and weld metal in a Ni-steel joint is performed in accordance with JIS Z 2244:2009 using a sample in which the macrostructure is revealed by the Nital method in accordance with JIS G 0553:2019. As described above, the measurement location for the Vickers hardness of the base material, HAZ, and weld metal is determined at the t / 2 section, t / 4 section, or the position where the distance from the center position in the plate thickness direction of the root face to the surface further away is 1 / 2, depending on the position of the root face in the plate thickness direction of the improvement; however, in a Ni-steel joint after welding, the root face may not be clear. Therefore, in the Ni-steel joint according to the present embodiment, the root face is set to the position where the width of the weld metal with the macrostructure (length of the weld metal along the butting direction) in the cross-section along the direction in which the base material of the Ni-steel joint is butted is minimized.
[0171] Here, with reference to FIG. 2, the measurement location of Vickers hardness is described in detail. FIG. 2 is a schematic diagram illustrating an example of an X-shaped groove. For example, in FIG. 2, the width of the weld metal (3) is minimized at the t / 2 portion. Therefore, the root face position (5) is the t / 2 portion where the width of the weld metal (3) is minimized. Since the root face position (5) of the groove is the center portion (t / 2 portion) of the plate thickness of the base material portion (1), the measurement location (6) of Vickers hardness is the t / 4 portion. At this time, there is a t / 4 portion at the t / 4 position from one surface and a t / 4 portion at the t / 4 position from the other surface, but Vickers hardness may be measured at either t / 4 portion. The measurement of the Vickers hardness of the weld metal (3) is performed at intervals of 0.5 mm from point P, where the measurement location (6) of the Vickers hardness and the fusion line (4), which is the interface between the HAZ (2) and the weld metal (3), intersect, up to at least the center of the weld metal (3) in the width direction. The Vickers hardness of the weld metal (3) is the arithmetic mean of the measured values. The measurement of the Vickers hardness of the base material (1) and the HAZ (2) is performed at intervals of 0.5 mm in the direction of the base material (1) from the location (point P) where the measurement of the Vickers hardness of the weld metal (3) was started, until the variation of the measured value is within the error range. If the absolute value of the difference between each of the 5 measured values and the arithmetic mean value is at most 5% or less of the arithmetic mean value, the variation of the measured value is considered to be within the error range. The Vickers hardness of the base material (1) is the measured value of the area where the variation of the measured value is within the error range. Vickers hardness is measured under a load of 1 kg.
[0172] (Effective crystal grain size at the maximum Vickers hardness of the HAZ: 2.0㎛ or more, 18.0㎛ or less)
[0173] When the HAZ becomes coarse, fracture is more likely to occur in the HAZ. The effective grain size of the region where the Vickers hardness of the HAZ reaches its maximum value (embrittlement region) is preferably 18.0 μm or less from the perspective of improving the cryogenic toughness of the Ni steel joint. The region where the Vickers hardness of the HAZ reaches its maximum value refers to the region where the Vickers hardness of the HAZ, measured by the above method, reaches its maximum value. The effective grain size of the embrittlement region is more preferably 12.0 μm or less, and even more preferably 8.0 μm or less. Since the effective grain size of the HAZ does not become smaller than the effective grain size of the base material, the effective grain size of the embrittlement region is, for example, 2.0 μm or more. The effective grain size of the embrittlement region is achieved by refining the effective grain size of the base material, and in the manufacture of the base material that is the material for the Ni steel joint, means that entail an increase in manufacturing costs, such as increasing the number of heat treatments, become necessary. The effective crystal grain size of the embrittlement part may be 3.0 μm or more, 4.0 μm or more, or 5.0 μm or more from the perspective of manufacturing costs. In this embodiment, the effective crystal grain size is defined as the circle equivalent diameter of a region (effective crystal grain) surrounded by a boundary of a metal structure having an orientation difference of 15° or more.
[0174] The effective grain size is measured using an Electron Back Scatter Diffraction (EBSD) analysis device attached to a scanning electron microscope. The measurement of the effective grain size is performed by using a plane (L-plane) that is perpendicular to the welding direction and perpendicular to the surface of the base material, and which includes the region where the Vickers hardness of the HAZ reaches its maximum value, as the observation plane. Using the EBSD analysis device, at least 5 fields of view are observed at a magnification of 2000x. Grains surrounded by grain boundaries at the boundaries of the metal structure having an orientation difference of 15° or more are considered as effective grains, and the circular equivalent diameter (effective grain size) of the effective grains is determined by image processing, and an arithmetic mean value is calculated. Image processing is performed in the same manner as the image processing used to calculate the average value of the circular equivalent diameter of the old austenite in the base material.
[0175] [Welding Metal]
[0176] Next, the chemical composition of the weld metal of the Ni-steel joint according to the present embodiment will be described. The weld metal is formed by melting the base material, which is the material of the Ni-steel joint, and the welding material. Unless otherwise noted, the following description of the chemical composition describes the chemical composition of the weld metal, and "mass%" is indicated as "%".
[0177] (C: 0.01% or more, 0.30% or less)
[0178] C is an element that increases the strength of the weld metal. The C content is 0.01% or more from the perspective of securing the strength of the Ni-steel joint by increasing the strength of the weld metal. The C content is preferably 0.02% or more, and more preferably 0.04% or more. On the other hand, if the C content is excessive, the cryogenic toughness of the Ni-steel joint decreases due to the formation of cementite. The C content is 0.30% or less from the perspective of securing the cryogenic toughness of the Ni-steel joint. The C content is preferably 0.20% or less, more preferably 0.10% or less, and even more preferably 0.05% or less.
[0179] (Si: 0.03% or more, 0.75% or less)
[0180] Si is a deoxidizing element that suppresses defects in the weld metal, such as blowholes. The Si content is 0.03% or more from the perspective of ensuring cryogenic toughness of the Ni-steel joint. The Si content is preferably 0.05% or more, and more preferably 0.10% or more. On the other hand, Si is an element that hardens the weld metal and reduces toughness. The Si content is 0.75% or less from the perspective of ensuring cryogenic toughness of the Ni-steel joint. The Si content is preferably 0.60% or less, and more preferably 0.50% or less.
[0181] (Mn: 0.1% or more, 17.0% or less)
[0182] Mn is a deoxidizing element that suppresses defects in the weld metal, such as blowholes, and is also an element that stabilizes austenite. The Mn content is 0.1% or more from the perspective of securing the strength and cryogenic toughness of the Ni steel joint. The Mn content is preferably 0.5% or more, and more preferably 1.0% or more. When the Ni content is 18.0% or less, the Mn content may be 7.0% or more or 10.0% or more from the perspective of stabilizing the austenite of the weld metal. On the other hand, Mn is an element that has a smaller effect on increasing toughness than Ni, and if the Mn content is excessive, the cryogenic toughness of the Ni steel joint decreases. The Mn content is 17.0% or less from the perspective of securing the cryogenic toughness of the Ni steel joint. The Mn content is preferably 16.0% or less, and more preferably 15.0% or less. When the Ni content is 40.0% or more, the Mn content may be 4.0% or less, or 3.5% or less.
[0183] (Ni: 8.0% or more, 85.0% or less)
[0184] Ni is an important element that stabilizes austenite and improves the cryogenic toughness of the weld metal. The Ni content is 8.0% or more from the perspective of ensuring cryogenic toughness of Ni steel joints. The Ni content is preferably 40.0% or more, more preferably 50.0% or more, and even more preferably 60.0% or more. Since Ni is an expensive element, the Ni content is 85.0% or less from the perspective of economic feasibility. The Ni content is preferably 80.0% or less. When the Mn content is 7.0% or more, the Ni content may be 18.0% or less, or 16.0% or less.
[0185] (Mn+Ni: 15.0% or more, 90.0% or less)
[0186] The total content of Mn and Ni is 15.0% or more from the perspective of securing cryogenic toughness of the Ni steel joint through the stabilization of the austenite of the weld metal. The total content of Mn and Ni is preferably 16.0% or more, more preferably 17.0% or more, and even more preferably 18.0% or more. Meanwhile, from the perspective of securing chemical composition that improves the strength of the Ni steel joint, the total content of Mn and Ni is 90.0% or less. The total content of Mn and Ni is preferably 85.0% or less, more preferably 80.0% or less, and even more preferably 75.0% or less.
[0187] (P: 0.020% or less)
[0188] P is an impurity, and if the P content is excessive, high-temperature cracking occurs in the weld metal, which reduces the cryogenic toughness of the Ni steel joint. The P content is 0.020% or less from the perspective of ensuring the cryogenic toughness of the Ni steel joint. The P content is preferably 0.015% or less, more preferably 0.010% or less, and even more preferably 0.005% or less. While it is preferable for the P content to be as low as possible, it may be 0.001% or more from the perspective of cost.
[0189] (S: 0.015% or less)
[0190] S is an impurity, and if the S content is excessive, high-temperature cracking occurs in the weld metal, which reduces the cryogenic toughness of the Ni steel joint. The S content is 0.015% or less from the perspective of ensuring the cryogenic toughness of the Ni steel joint. The S content is preferably 0.010% or less, more preferably 0.005% or less, and even more preferably 0.002% or less. While it is preferable for the S content to be lower, it may be 0.001% or more from the perspective of cost.
[0191] (N: 0.10% or less)
[0192] N is an element that increases the strength of the weld metal and also stabilizes austenite. When the Mn content is relatively high, for example, when the Mn content is 7.0% or higher, the N content can be increased; however, even if the Mn content is relatively high, if the N content is excessive, blowholes may occur in the weld metal, which may reduce the cryogenic toughness of the Ni-steel joint. From the perspective of ensuring the cryogenic toughness of the Ni-steel joint, the N content is 0.10% or less. The N content is preferably 0.05% or less, and more preferably 0.01% or less. When the Mn content is relatively low, for example, when the Mn content is 4.0% or less, blowholes in the weld metal may occur more easily due to N compared to when the Mn content is relatively high. Therefore, from the perspective of preventing the occurrence of blowholes, it is desirable to reduce the N content. From the perspective of cost, the N content may be 0.001% or higher.
[0193] The weld metal of the Ni steel joint according to the present embodiment contains one or more of Mo, W, Cr, and Nb as shown below in order to improve the strength or toughness of the Ni steel joint.
[0194] (Mo: 0% or more, 22.0% or less)
[0195] Mo is an element that increases the corrosion resistance or strength of the weld metal. The lower limit of the Mo content is not limited and may be 0%. The Mo content is preferably 1.0% or more, more preferably 9.0% or more, and even more preferably 12.0% or more. On the other hand, if the Mo content is excessive, the cryogenic toughness of the Ni steel joint may decrease due to the hardening of the weld metal and the formation of precipitates. From the perspective of ensuring the cryogenic toughness of the Ni steel joint, the Mo content is 22.0% or less. Since Mo is an expensive element, if Cr and Nb are included as described later, the Mo content may be 9.0% or less from the perspective of economic feasibility. The Mo content may be 7.0% or less, or 5.0% or less.
[0196] (W: 0% or more, 5.0% or less)
[0197] W is an element that increases the strength of the weld metal. The lower limit of the W content is not limited and may be 0%. The W content is preferably 0.9% or more, and more preferably 2.0% or more. On the other hand, if the W content is excessive, the cryogenic toughness of the Ni steel joint may decrease due to the hardening of the weld metal. From the perspective of ensuring the cryogenic toughness of the Ni steel joint, the W content is 5.0% or less. The W content is preferably 4.0% or less, and more preferably 3.0% or less.
[0198] (Cr: 0% or more, 17.0% or less)
[0199] Cr is an element that increases the corrosion resistance or strength of the weld metal. The lower limit of the Cr content is not limited and may be 0%. The Cr content is preferably 2.0% or more, more preferably 6.0% or more, and even more preferably 8.0% or more. On the other hand, if the Cr content is excessive, the cryogenic toughness of the Ni-steel joint may decrease due to the hardening of the weld metal and the formation of precipitates. From the perspective of ensuring the cryogenic toughness of the Ni-steel joint, the Cr content is 17.0% or less. The Cr content is preferably 15.0% or less, and more preferably 12.0% or less.
[0200] (Nb: 0% or more, 3.0% or less)
[0201] Nb is an element that increases the strength of the weld metal. The lower limit of the Nb content is not limited and may be 0%. The Nb content is preferably 0.2% or more, and more preferably 1.0% or more. On the other hand, if the Nb content is excessive, the cryogenic toughness of the Ni steel joint may decrease due to the hardening of the weld metal and the formation of precipitates. From the perspective of ensuring the cryogenic toughness of the Ni steel joint, the Nb content is 3.0% or less. The Nb content is preferably 2.5% or less, and more preferably 2.0% or less.
[0202] (Total content of one or more of Mo, W, Cr, and Nb: 2.0% or more)
[0203] The total content of one or more of Mo, W, Cr, and Nb is 2.0% or more from the perspective of securing the strength of the Ni steel joint by increasing the strength of the weld metal. The total content of one or more of Mo, W, Cr, and Nb is preferably 6.0% or more, more preferably 7.0% or more, and even more preferably 10.0% or more. When the weld metal contains two types of Cr and Nb, the total content of Cr and Nb is preferably 6.2% or more. When the weld metal contains two types of Mo and W, the total content of Mo and W is preferably 9.9% or more. The total content of one or more of Mo, W, Cr, and Nb is preferably 50.0% or less, more preferably 30.0% or less, and even more preferably 25.0% or less.
[0204] The weld metal of the Ni steel joint according to the present embodiment contains the above chemical components, and the remainder consists of Fe and impurities. Chemical components that may be incorporated into the weld metal as impurities include, for example, Sb, Sn, As, Co, Zn, etc. The Sb content, Sn content, and As content that are permissible within a range that does not adversely affect the Ni steel joint according to the present embodiment are each 0.003% or less. Likewise, the Co content and Zn content are each 0.01% or less.
[0205] The chemical composition of the weld metal is, for example
[0206] C: 0.01% or more, 0.15% or less,
[0207] Si: 0.03% or more, 0.75% or less,
[0208] Mn: 0.1% or more, 4.0% or less,
[0209] Ni: 40.0% or more, 85.0% or less,
[0210] Mo: 9.0% or more, 22.0% or less,
[0211] W: 0.9% or more, 5.0% or less,
[0212] Cr: 0% or more, 4.0% or less,
[0213] Nb: 0% or more, 3.0% or less,
[0214] P: 0.020% or less,
[0215] S: 0.015% or less,
[0216] N: 0.010% or less,
[0217] O: 0% or more, 0.1% or less,
[0218] Remainder: May consist of Fe and impurities.
[0219] If the chemical composition of the weld metal is within the above range, superior cryogenic toughness can be obtained.
[0220] In addition, the chemical composition of the weld metal is, for example,
[0221] C: 0.01% or more, 0.15% or less,
[0222] Si: 0.03% or more, 0.75% or less,
[0223] Mn: 0.1% or more, 4.0% or less,
[0224] Ni: 40.0% or more, 85.0% or less,
[0225] Cr: 6.0% or more, 17.0% or less,
[0226] Mo: 0% or more, 9.0% or less,
[0227] W: 0% or more, 5.0% or less,
[0228] Nb: 0.2% or more, 3.0% or less,
[0229] P: 0.020% or less,
[0230] S: 0.015% or less,
[0231] N: 0.010% or less,
[0232] O: 0% or more, 0.1% or less,
[0233] Remainder: May consist of Fe and impurities.
[0234] If the chemical composition of the weld metal is within the above range, excellent cryogenic toughness can be obtained while suppressing the increase in cost.
[0235] In addition, the chemical composition of the weld metal is, for example,
[0236] C: 0.01% or more, 0.30% or less,
[0237] Si: 0.03% or more, 0.75% or less,
[0238] Mn: 7.0% or more, 17.0% or less,
[0239] Ni: 8.0% or more, 18.0% or less,
[0240] Cr: 2.0% or more, 12.0% or less,
[0241] Nb: 0% or more, 3.0% or less,
[0242] W: 0% or more, 5.0% or less,
[0243] Mo: 0% or more, 5.0% or less,
[0244] P: 0.020% or less,
[0245] S: 0.015% or less,
[0246] N: 0.10% or less,
[0247] O: 0% or more, 0.1% or less,
[0248] Remainder: May consist of Fe and impurities.
[0249] If the chemical composition of the weld metal is within the above range, cryogenic toughness can be secured while further suppressing the increase in cost.
[0250] (Proportion of body-centered cubic structure in the weld metal microstructure: 10% or less)
[0251] The proportion of a body-centered cubic (BCC) structure in the microstructure of the weld metal of the Ni steel joint according to the present embodiment is 10% or less. Since BCC has lower toughness compared to face-centered cubic (FCC), if the proportion of a body-centered cubic structure is high, cracks are more likely to occur starting from there. Therefore, the proportion of a body-centered cubic structure in the microstructure of the weld metal is 10% or less. The proportion of a body-centered cubic structure in the microstructure of the weld metal is preferably 5% or less, more preferably 2% or less, and even more preferably 0%.
[0252] The metal structure of the weld metal is mainly derived from the chemical composition of the weld metal. The range of the chemical composition of the weld metal according to the present embodiment described so far includes both the region where the body-centered cubic (BCC) structure in the metal structure is 10% or less and the region where it exceeds 10%. As described above, in the region where the body-centered cubic (BCC) structure in the metal structure of the weld metal exceeds 10%, cracks are prone to occur in the weld metal, and thus the effects of the present invention are not obtained.
[0253] In terms of chemical composition, it is difficult to clearly separate the region where the body-centered cubic (BCC) structure in the metal structure is 10% or less from the region where it exceeds 10%. In this embodiment, the chemical composition is substantially limited by defining the fraction of the metal structure of the weld metal.
[0254] The proportion of the body-centered cubic structure in the microstructure of the weld metal is measured by the following method. Specifically, a ferrite microstructure quantity measuring instrument (FERITSCOPE (registered trademark) FMP30) manufactured by Fischer Instruments Co., Ltd. is used, and the ratio of BCC is measured by using a probe (FGAB 1.3-Fe) manufactured by Fischer Instruments Co., Ltd. on the probe of said measuring instrument. This is an instrument that measures the ferromagnetic content of the metal microstructure using magnetic induction, and quantifies and displays the ratio of BCC, which is a ferromagnetic material in the surface layer (the region up to about 1.5 mm below the surface). The microstructure constituting the weld metal of the Ni steel joint according to the present embodiment consists of two phases of FCC and BCC, or FCC alone.
[0255] [Method for manufacturing Ni steel joints]
[0256] Next, an example of a method for manufacturing a Ni-steel joint according to the present embodiment will be described. The Ni-steel joint according to the present embodiment can be effective if it has the above-described configuration, regardless of the manufacturing method.
[0257] First, an example of a method for manufacturing a base material that serves as the material for the Ni-steel joint according to the present embodiment will be explained. Hereinafter, the base material that serves as the material for the Ni-steel joint may be referred to simply as the base material.
[0258] In the present embodiment, for the manufacture of the base material, a steel billet produced by, for example, a steel flux and continuous casting is used. The base material is manufactured, for example, by hot rolling and heat treatment of the steel billet. After hot rolling, accelerated cooling, such as water cooling, is preferably performed. The heat treatment includes, for example, a first heat treatment performed at a higher temperature and a second heat treatment performed at a lower temperature. There are cases where only one of the first or second heat treatment is performed, or cases where both are performed. In the first or second heat treatment, after holding at the heating temperature, accelerated cooling, such as water cooling, is preferably performed.
[0259] Hereinafter, preferred manufacturing conditions for each process of the method for manufacturing the base material in the present embodiment will be described.
[0260] (Heating temperature of steel billets used for hot rolling: 950℃ or higher, 1160℃ or lower)
[0261] (Duration: 20 minutes or more, 180 minutes or less)
[0262] The heating temperature of the steel billet during hot rolling is preferably 950°C or higher from the perspective of reducing the load on the rolling mill. Meanwhile, the heating temperature of the steel billet during hot rolling is preferably 1160°C or lower from the perspective of refining the old austenite of the base material. The holding time at the heating temperature is preferably 20 minutes or more from the perspective of homogenizing the temperature of the steel billet. The holding time at the heating temperature is preferably 180 minutes or less from the perspective of cost.
[0263] (Cumulative reduction rate at 950℃ or below during hot rolling: 90% or more, 95% or less)
[0264] The cumulative reduction rate at 950°C or lower during hot rolling is preferably 90% or higher from the perspective of refining the old austenite of the base material. Meanwhile, the cumulative reduction rate at 950°C or lower during hot rolling is preferably 95% or lower from the perspective of cost. The cumulative reduction rate at 950°C or lower during hot rolling is calculated from the plate thickness at 950°C and the plate thickness at the end of hot rolling.
[0265] (Hot rolling end temperature: 680℃ or higher, 850℃ or lower)
[0266] The end temperature of hot rolling is preferably 680°C or higher and 850°C or lower from the perspective of securing the yield stress of the base material at room temperature and the cryogenic toughness of the base material. The end temperature of hot rolling is preferably 680°C or higher from the perspective of preventing a decrease in the initiation temperature of accelerated cooling. Meanwhile, the end temperature of hot rolling is preferably 850°C or lower from the perspective of suppressing the recovery of dislocations introduced by rolling.
[0267] (Accelerated cooling start temperature after hot rolling: 580℃ or higher)
[0268] Accelerated cooling after hot rolling is performed, for example, by water cooling. The starting temperature of accelerated cooling is preferably 580°C or higher from the perspective of securing yield stress at room temperature. The starting temperature of accelerated cooling does not exceed the ending temperature of hot rolling. The cooling rate of accelerated cooling is preferably 10°C / second or higher. The cooling rate of accelerated cooling is the average value from the start to the end of accelerated cooling. There is no particular upper limit for the cooling rate of accelerated cooling, but it may be 50°C / second or lower. The ending temperature of accelerated cooling is preferably 200°C or lower from the perspective of promoting martensitic transformation of the base material.
[0269] (Holding temperature for the first heat treatment: 610℃ or higher, 650℃ or lower)
[0270] (Duration: 20 minutes or more, 180 minutes or less)
[0271] The first heat treatment is performed after accelerated cooling following hot rolling. The first heat treatment is effective for securing retained austenite, which improves the cryogenic toughness of the base material.
[0272] The heating rate to the holding temperature can be, for example, 1°C / min or more and 50°C / min or less. In terms of heating time, the heating rate to the holding temperature is preferably 5°C / min or more, and more preferably 10°C / min or more. In addition, in terms of economic efficiency, the heating rate to the holding temperature is preferably 40°C / min or less, and more preferably 30°C / min or less.
[0273] The holding temperature of the first heat treatment is preferably 610°C or higher and 650°C or lower. The holding temperature of the first heat treatment is preferably 610°C or higher from the perspective of promoting austenite transformation. Meanwhile, the holding temperature of the first heat treatment is preferably 650°C or lower from the perspective of stabilizing austenite.
[0274] The holding time of the first heat treatment is preferably 20 minutes or more and more preferably 60 minutes or more from the perspective of securing austenite. Meanwhile, the holding time of the first heat treatment is preferably 180 minutes or less and more preferably 120 minutes or less from the perspective of suppressing the precipitation of carbides.
[0275] The cooling rate during accelerated cooling after holding the first heat treatment is preferably 8°C / sec or higher from the perspective of preventing tempering embrittlement. The cooling rate of accelerated cooling is the average value from the start to the end of accelerated cooling. There is no particular upper limit for the cooling rate of accelerated cooling, and the cooling rate may be, for example, 50°C / sec or lower. The end temperature of accelerated cooling is preferably 200°C or lower.
[0276] (Holding temperature for the second heat treatment: 530℃ or higher, 570℃ or lower)
[0277] (Duration: 20 minutes or more, 180 minutes or less)
[0278] The second heat treatment is performed after accelerated cooling following hot rolling or after the first heat treatment, but preferably after the first heat treatment. The second heat treatment is effective for securing retained austenite, which improves the cryogenic toughness of the base material.
[0279] The heating rate to the holding temperature can be, for example, 1°C / min or more and 50°C / min or less. In terms of heating time, the heating rate to the holding temperature is preferably 5°C / min or more, and more preferably 10°C / min or more. In addition, in terms of economic efficiency, the heating rate to the holding temperature is preferably 40°C / min or less, and more preferably 40°C / min or less.
[0280] The holding temperature of the second heat treatment is preferably 530°C or higher and 570°C or lower from the perspective of improving the cryogenic toughness of the base material. The holding temperature of the second heat treatment is preferably 530°C or higher from the perspective of stabilization by C enrichment into austenite. The holding temperature of the second heat treatment is preferably 570°C or lower from the perspective of suppressing the formation of hard martensite.
[0281] The holding time of the second heat treatment is preferably 20 minutes or more and more preferably 60 minutes or more from the perspective of stabilizing the austenite. Meanwhile, the holding time of the second heat treatment is preferably 180 minutes or less and more preferably 120 minutes or less from the perspective of suppressing the precipitation of carbides.
[0282] The cooling rate of accelerated cooling after holding the second heat treatment is preferably 5°C / sec or higher from the perspective of preventing tempering embrittlement. The cooling rate of accelerated cooling is the average value from the start to the end of accelerated cooling. There is no particular upper limit for the cooling rate of accelerated cooling, and the cooling rate may be, for example, 50°C / sec or lower. The end temperature of accelerated cooling is preferably 200°C or lower.
[0283] Up to this point, an example of a method for manufacturing the base material has been explained.
[0284] The welding material used for manufacturing Ni steel joints is selected considering the dilution of the chemical composition by the base material. The chemical composition of the welding material is, for example in mass%, C: 0.01% or more, 0.33% or less; Si: 0.03% or more, 0.83% or less; Mn: 0.1% or more, 18.9% or less; Ni: 8.9% or more, 94.4% or less; S: 0.015% or less; Mo: 0% or more, 24.4% or less; W: 0% or more, 5.6% or less; Cr: 0% or more, 18.9% or less; Nb: 0% or more, 3.3% or less; the sum of the contents of Mo, W, Cr, and Nb is 2.2% or more; N: 0.1% or less; and the remainder is Fe and impurities. When the chemical composition of the welding material does not contain Cr or Nb, preferably Mo: 10.0% or more and 24.4% or less, and W: 1.0% or more and 5.6% or less. When the chemical composition of the welding material does not contain Mo or W, preferably Cr: 6.7% or more and 18.9% or less, and Nb: 0.2% or more and 3.3% or less.
[0285] The welding method is, for example, shielded metal arc welding, submerged arc welding, TIG welding (Tungsten Inert Gas Welding), MUG welding (Metal Active Gas Welding), or electro-gas arc welding. The groove shape is any of a single V groove, a single bevel groove, a single J groove, a single U groove, a double V groove, a double bevel groove, a double J groove, or a double U groove. The groove shape is preferably an X groove, and the groove angle is, for example, 60°. The welding heat input is preferably 10 kJ / cm or more, and more preferably 20 kJ / cm or more, from the perspective of work efficiency. Meanwhile, the welding heat input is 30 kJ / cm or less, from the perspective of improving the cryogenic toughness of the Ni steel joint.
[0286] Examples
[0287] Examples of the present invention are described below. The examples described below are illustrative of the present invention, and the present invention is not limited to the examples described below.
[0288] Steel billets with a thickness of 150 mm to 400 mm were manufactured by melting steel in a converter and continuous casting. The steel billets were heated, hot-rolled, and heat-treated to produce steel plates. The heating temperature for hot rolling was within the range of 950°C or higher and 1160°C or lower, and the holding time was within the range of 20 minutes or higher and 180 minutes or lower. The cumulative reduction rate at 950°C or lower was within the range of 90% or higher and 95% or lower, and the end temperature of hot rolling was within the range of 680°C or higher and 850°C or lower. The starting temperature for accelerated cooling after hot rolling was 580°C or higher and below the end temperature of hot rolling. The end temperature for accelerated cooling after hot rolling was 200°C or lower. The cooling rate of accelerated cooling after hot rolling (average value from start to end) was 10°C / second or higher.
[0289] After that, a first heat treatment was performed, and a second heat treatment was performed after the first heat treatment.
[0290] The heating rate in the first heat treatment was within the range of 1°C / min or more and 50°C / min or less, the holding temperature in the first heat treatment was within the range of 610°C or more and 650°C or less, and the holding time at the holding temperature in the first heat treatment was within the range of 20 minutes or more and 180 minutes or less. The cooling rate of accelerated cooling after holding at the holding temperature in the first heat treatment (average value from start to end) was 8°C / second or more. The end temperature of accelerated cooling after holding at the temperature in the first heat treatment was 200°C or less.
[0291] The heating rate in the second heat treatment was within the range of 1°C / min or more and 50°C / min or less, and the holding temperature of the second heat treatment was within the range of 530°C or more and 570°C or less. The holding time at the above holding temperature in the second heat treatment was within the range of 20 minutes or more and 180 minutes or less. The cooling rate of accelerated cooling after holding the second heat treatment was 5°C / second or more. The end temperature of accelerated cooling after holding the second heat treatment was 200°C or less.
[0292] Samples were taken from each steel plate manufactured in the above process, and the content of each chemical component was measured. The chemical composition of each steel plate is shown in Tables 1A and 1B. Furthermore, it is obvious that the chemical composition of each steel plate is identical to the chemical composition of the base material after each steel plate is welded. Therefore, the chemical compositions shown in Tables 1A and 1B represent the chemical composition of the base material of the Ni steel joint. Blank spaces in Tables 1A and 1B indicate that the corresponding element was not intentionally added. Additionally, underlined numbers in Table 1B indicate that they are outside the scope of the present invention.
[0293] [Table 1A]
[0294]
[0295] [Table 1B]
[0296]
[0297] A sample for microstructure observation was taken from the steel plate, and the circular equivalent diameter of the old austenite was measured with the center of the plate thickness in the L cross-section as the observation surface. The measurement of the circular equivalent diameter of the old austenite was performed by scanning electron microscopy after etching the observation surface with a saturated aqueous picric acid solution to reveal the old austenite grain boundaries. SEM observation was performed at a magnification of 1,000x or 2,000x, and SEM images of five or more fields were captured. The circular equivalent diameter of the old austenite was defined as the arithmetic mean of the measured values obtained through image processing of the SEM images. The grain boundary lines of the old austenite were determined by EBSD analysis by specifying the crystal orientations of martensite and retained austenite within a 200㎛×200㎛ range in each field, determining the crystal orientation of the old austenite within the said range, and defining the line where the difference in crystal orientation of the old austenite was 15° or more as the old austenite grain boundary. The area of spherical austenite existing within the above range of each field of view is calculated using image analysis software, and from the calculated area S, the average value S of the area of spherical austenite A ...was calculated. Then, setting the average value of the circular equivalent diameter of the spherical austenite as D, D=2×√(π×S A From ), the average value D of the original equivalent diameter of the austenite was calculated.
[0298] The volume fraction of retained austenite was measured by X-ray diffraction. The volume fraction of retained austenite was determined from the ratio of the integrated intensities of the X-ray peaks of austenite (face-centered cubic structure) and tempered martensite (body-centered cubic structure). Specifically, the volume fraction of retained austenite was determined from the ratio of the integrated intensities of the (111), (200), and (211) planes of the ferrite phase (α phase) with a BCC structure to the integrated intensities of the (111), (200), and (220) planes of the austenite phase (γ phase) with an FCC structure.
[0299] Tensile testing was performed in accordance with JIS Z 2241:2011 in a room controlled to 20°C by an air conditioner, and the yield stress of the steel plate was measured. The specimens used for the tensile test were No. 1A full-thickness tensile specimens. The longitudinal direction of the specimen was parallel to the rolling direction (L direction), and the specimen was taken at the 1 / 4t section. The yield stress was the average of the measurements from two specimens. If no clear lower yield stress was observed, the yield stress was assumed to be 0.2% yield strength. Cryogenic toughness was evaluated using full-thickness CT (Compact Tension) specimens ground by 0.5 mm from each side. The notch entry direction of the CT specimen was perpendicular to the rolling direction (C direction). In liquid hydrogen (-253℃), a JR curve was prepared according to the unloading compliance method specified in ASTM standard E1820-13, and the J value was converted into a KIC value. The target value for cryogenic toughness was set to 150 MPa·√m or higher.
[0300] An X-bevel process with a bevel angle of 60° was performed on a steel plate, and a Ni steel joint was manufactured by shielded arc welding. The welding heat input was set to be 20 kJ / cm or higher and 30 kJ / cm or lower. The chemical composition of the welding material in Tables 2A and 2B was defined as the content of C, Si, Mn, Ni, Mo, W, Cr, Nb, and N measured using a sample taken from the welding material. The content of each chemical component of the weld metal in Tables 2A and 2B was defined as the content of C, Si, Mn, Ni, P, S, N, Mo, W, Cr, and Nb measured using a sample taken from the weld metal of the Ni steel joint. The measurement of Vickers hardness of the base metal, HAZ, and weld metal in Ni steel joints was performed in accordance with JIS Z 2244:2009 using a sample in which the macrostructure was revealed by the Nital method in accordance with JIS G 0553:2019.
[0301] In addition, the ratio of the body-centered cubic structure in the weld metal after welding was completed was measured. The center of the weld metal in the width direction from the surface of the weld joint was measured as the measurement point. Using the aforementioned ferrite microstructure measuring instrument (FERITSCOPE (registered trademark) FMP30), the ratio of BCC was measured by using a probe (FGAB 1.3-Fe) manufactured by Fisher Instruments Co., Ltd. on the probe of the measuring instrument.
[0302] Upon observing the cross-section along the direction in which the base metal was butted, the width of the weld metal with a macrostructure was minimized at the t / 2 point in the plate thickness direction; therefore, the measurement location for Vickers hardness in the plate thickness direction was set to the t / 4 point. Additionally, the measurement load was set to 9.8 N (1 kg). The measurement of the Vickers hardness of the weld metal was performed at the t / 4 point at intervals of 0.5 mm from the fusion line to the center of the weld metal in the width direction. The measurement of Vickers hardness of the base metal and the HAZ was performed at the t / 4 point at intervals of 0.5 mm from the fusion line until the variation in the measurement value was within the error range. The Vickers hardness of the base metal was taken as the measurement value at the point where the variation in the measurement value was within the error range. The Vickers hardness of the HAZ was taken as the maximum value of Vickers hardness measured in the HAZ. When the Vickers hardness of the HAZ is greater than that of the weld metal and base metal, the arithmetic mean of the Vickers hardness of the base metal and the Vickers hardness of the weld metal was calculated, and the ratio of the Vickers hardness of the HAZ to this was calculated.
[0303] The effective grain size of the embrittlement zone where the Vickers hardness of the HAZ is at its maximum was measured using an EBSD analysis device. Observations were performed at a magnification of 2000x and at least 5 fields of view, and the boundaries of the metal structure having an orientation difference of 15° or more were considered as grain boundaries. The grains surrounded by these grain boundaries were considered as effective grains, and the original equivalent grain size (diameter) was determined from their areas by image processing. The effective grain size was defined as the arithmetic mean of the original equivalent diameters of the regions surrounded by grain boundaries having an orientation difference of 15° or more.
[0304] The cryogenic toughness of the Ni steel joint was evaluated using a CT test specimen of the full thickness, ground by 0.5 mm from each side. The depth direction of the notch in the CT test specimen was set to the welding direction (C direction). As shown in FIG. 3, the notch (8) of the CT test specimen extends along the plate thickness direction, and the cutting direction of the notch (8) is perpendicular to the plate thickness plane. The notch (8) includes an embrittlement portion (7) where the Vickers hardness is maximum at the t / 4 portion. In liquid hydrogen (-253°C), a JR curve was prepared according to the unloading compliance method specified in ASTM standard E1820-13, and the J value K IC It was converted into a value. The target value for cryogenic toughness is 150 MPa·√m or higher. The test results for the base material and Ni steel joint are shown in Tables 3A and 3B. In addition, in Tables 3A and 3B, "spherical γ grain size" represents the average value of the circular equivalent diameter of the spherical austenite, "yield stress" represents the yield stress at 20°C, and "Vickers hardness ratio" represents the value of the ratio of the Vickers hardness of the weld heat-affected zone to the arithmetic mean of the Vickers hardness of the base material and the Vickers hardness of the weld metal.
[0305] [Table 2A]
[0306]
[0307] [Table 2B]
[0308]
[0309] [Table 3A]
[0310]
[0311] [Table 3B]
[0312]
[0313] In all examples, the proportion of residual austenite in the base material was 2.0 volume% or more and 20.0 volume% or less. In addition, as shown in Tables 3A and 3B, the cryogenic toughness of the base materials and Ni steel joints of No. 1 to 26 was 150 MPa·√m or more. In No. 23, the low carbon content in the base material resulted in a low yield stress, causing the base material to deform preferentially; therefore, the cryogenic toughness of the Ni steel joint was also better than that of other Ni steel joints. In No. 1 to 25, the hardness of the embrittled part was 1.2 times or more than the average value of the hardness of the base material and the weld metal, and the cryogenic toughness was better than that of the Ni steel joint of No. 26. In the case of the Ni steel joint of No. 26, the C content of the base metal is low, so the Vickers hardness of the embrittled part is low; therefore, compared to the Ni steel joints of No. 1 to 25, it is thought that the hardness of the embrittled part relative to the average value of the hardness of the base metal and the weld metal has decreased. On the other hand, Nos. 101 to 108 are examples where the chemical composition of the base metal is inappropriate, and the cryogenic toughness of the Ni steel joint is reduced. Nos. 109 to 115 are examples where the chemical composition of the weld metal is inappropriate, and the cryogenic toughness of the Ni steel joint was reduced. Industrial applicability
[0314] The low-temperature nickel-containing steel welded joint according to the present invention is used, for example, in liquid hydrogen tanks. The low-temperature nickel-containing steel welded joint according to the present invention has a high yield stress at room temperature, which enables the enlargement and weight reduction of liquid hydrogen tanks. By enlarging the liquid hydrogen tank, the surface area relative to the volume is reduced, and an improvement in heat dissipation performance can be expected. By reducing the weight of the liquid hydrogen tank, an improvement in the fuel efficiency of liquid hydrogen carriers can be expected. Explanation of the symbols
[0315] 1: Mother material 2: Welding Heat Affected Zone 3: Welding metal 4: Fusion Line 5: Position of the root plane of the improvement in the plate thickness direction 6: Vickers hardness measurement location 7: Fire-breathing unit 8: Notch
Claims
Claim 1 The apparatus comprises a base material, a weld heat-affected zone, and a weld metal, wherein the chemical composition of the base material, in mass%, is: C: 0.010% or more, 0.070% or less; Si: 0.03% or more, 0.30% or less; Mn: 0.10% or more, 0.80% or less; Ni: 10.5% or more, 17.4% or less; Al: 0.010% or more, 0.060% or less; N: 0.0015% or more, 0.0060% or less; O: 0.0030% or less; P: 0.0080% or less; S: 0.0040% or less; Cu: 0% or more, 1.00% or less; Cr: 0% or more, 1.00% or less; Mo: 0% or more, 0.60% or less; Nb: 0% or more, 0.050% or less; V: Composed of 0% or more, 0.080% or less, Ti: 0% or more, 0.020% or less, B: 0% or more, 0.0020% or less, Ca: 0% or more, 0.0040% or less, REM: 0% or more, 0.0050% or less, remainder: Fe and impurities, the average value of the original equivalent diameter of the old austenite in the base material is 3.0㎛ or more and 20.0㎛ or less, the yield stress of the base material at 20℃ is 460MPa or more and 710MPa or less, and the chemical composition of the weld metal is, in mass%, C: 0.01% or more, 0.30% or less, Si: 0.03% or more, 0.75% or less, Mn: 0.1% or more, 17.0% or less, Ni: 8.0% or more, 85.0% or less, and P: It is composed of 0.020% or less, S: 0.015% or less, N: 0.100% or less, Mo: 0% or more, 22.0% or less, W: 0% or more, 5.0% or less, Cr: 0% or more, 17.0% or less, Nb: 0% or more, 3.0% or less, with at least one of these having a total of 2.0% or more, O: 0% or more, 0.1% or less, and the remainder being Fe and impurities, wherein the proportion of a body-centered cubic structure in the microstructure of the weld metal is 10% or less, wherein the total content of Mn and Ni in the chemical composition of the weld metal is 15.0% or more and 90.0% or less, and the Mn content in the chemical composition of the weld metal is 4.A low-temperature nickel-containing steel welded joint in which, when 0% or less, the content of N in the chemical composition of the weld metal is 0.010% or less. Claim 2 A nickel-containing steel welded joint for low temperature, wherein the chemical composition of the weld metal in mass% comprises: C: 0.01% or more, 0.15% or less; Si: 0.03% or more, 0.75% or less; Mn: 0.1% or more, 4.0% or less; Ni: 40.0% or more, 85.0% or less; Mo: 9.0% or more, 22.0% or less; W: 0.9% or more, 5.0% or less; Cr: 0% or more, 4.0% or less; Nb: 0% or more, 3.0% or less; P: 0.020% or less; S: 0.015% or less; N: 0.010% or less; O: 0% or more, 0.1% or less; and the remainder: Fe and impurities. Claim 3 A nickel-containing steel welded joint for low temperature, wherein the chemical composition of the weld metal in mass% comprises: C: 0.01% or more, 0.15% or less; Si: 0.03% or more, 0.75% or less; Mn: 0.1% or more, 4.0% or less; Ni: 40.0% or more, 85.0% or less; Cr: 6.0% or more, 17.0% or less; Mo: 0% or more, 9.0% or less; W: 0% or more, 5.0% or less; Nb: 0.2% or more, 3.0% or less; P: 0.020% or less; S: 0.015% or less; N: 0.010% or less; O: 0% or more, 0.1% or less; and the remainder: Fe and impurities. Claim 4 A nickel-containing steel welded joint for low temperature, wherein, in mass%, the chemical composition of the weld metal comprises: C: 0.01% or more, 0.30% or less; Si: 0.03% or more, 0.75% or less; Mn: 7.0% or more, 17.0% or less; Ni: 8.0% or more, 18.0% or less; Cr: 2.0% or more, 12.0% or less; Nb: 0% or more, 3.0% or less; Mo: 0% or more, 5.0% or less; W: 0% or more, 5.0% or less; P: 0.020% or less; S: 0.015% or less; N: 0.10% or less; O: 0% or more, 0.1% or less; and the remainder: Fe and impurities. Claim 5 A low-temperature nickel-containing steel welded joint according to any one of claims 1 to 4, wherein the maximum value of the Vickers hardness of the weld heat-affected zone is 1.20 times or more and 3.00 times or less of the arithmetic mean value of the Vickers hardness of the base material and the Vickers hardness of the weld metal, and the effective crystal grain size of the region where the Vickers hardness of the weld heat-affected zone is at its maximum is 2.0 μm or more and 18.0 μm or less.
Citation Information
Patent Citations
Nickel-containing steel for low-temperature use
WO2019082322A1
Nickel-containing steel for use at low temperatures
WO2019082325A1